Hydrogel Electrolyte Enabled High‐Performance Flexible Aqueous Zinc Ion Energy Storage Systems toward Wearable Electronics - Weng, Gao; Yang, Xianzhong; Wang, Zhiqi; Xu, Yan; Liu, Ruiyuan (Small (Weinheim an der Bergstrasse, Germany), 2023)
To cater to the swift advance of flexible wearable electronics, there is growing demand for flexible energy storage system (ESS). Aqueous zinc ion energy storage systems (AZIESSs), characterizing safety and low cost, are competitive candidates for flexible energy storage. Hydrogels, as quasi‐solid substances, are the appropriate and burgeoning electrolytes that enable high‐performance flexible AZIESSs. However, challenges still remain in designing suitable and comprehensive hydrogel electrolyte, which provides flexible AZIESSs with high reversibility and versatility. Hence, the application of hydrogel electrolyte‐based AZIESSs in wearable electronics is restricted. A thorough review is required for hydrogel electrolyte design to pave the way for high‐performance flexible AZIESSs. This review delves into the engineering of desirable hydrogel electrolytes for flexible AZIESSs from the perspective of electrolyte designers. Detailed descriptions of hydrogel electrolytes in basic characteristics, Zn anode, and cathode stabilization effects as well as their functional properties are provided. Moreover, the application of hydrogel electrolyte‐based flexible AZIESSs in wearable electronics is discussed, expecting to accelerate their strides toward lives. Finally, the corresponding challenges and future development trends are also presented, with the hope of inspiring readers. This review focuses on hydrogel electrolytes engineering for high‐performance flexible aqueous zinc ion energy storage systems. From basic characteristics, anode and cathode stabilization effects, and functional properties, the corresponding mechanisms of designing desirable hydrogel electrolytes are elaborated. The application of flexible aqueous zinc ion energy storage systems in wearable electronics is also depicted with a bright future.